2015
DOI: 10.3920/qas2013.0265
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and dissipation of neonicotinoid insecticides on chilli fruits

Abstract: A field trial was conducted to study the dissipation of neonicotinoid insecticides, imidacloprid and acetamiprid, on chilli fruits for the estimation of its half-life and waiting period. The samples of chilli fruits drawn at 0, 1, 3, 5, 7, 15, 21 days after spraying were quantified on gas liquid chromatography equipped with Ni 63 electron capture detector for acetamiprid and high performance liquid chromatography for imidacloprid. The residues of imidacloprid persisted up to seven days, whereas the acetamiprid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Residues in tomato were at MRL after 6 days of treatment. (Varghese et al, 2015) studied the residues of acetamiprid on chili fruits. The half-life value of acetamiprid was 2.27 days, while a waiting period was 7.18 days.…”
Section: Acetamiprid Residuesmentioning
confidence: 99%
“…Residues in tomato were at MRL after 6 days of treatment. (Varghese et al, 2015) studied the residues of acetamiprid on chili fruits. The half-life value of acetamiprid was 2.27 days, while a waiting period was 7.18 days.…”
Section: Acetamiprid Residuesmentioning
confidence: 99%
“…Pesticide residues in food and their penetration into the food chain have sparked extensive public discussion. Few dissipation studies were performed to generate data on the effects of spiromesifen insecticides on chili fruits (Pathipati et al, 2017; Sharma, Rao, et al, 2007; Sushil et al, 2018; Varghese et al, 2011; VinothKumar, 2020; Viswanathan & Paul, 2020; Xavier & Chandran, 2016). Herein we report the dissipation kinetics and risk assessment of the effect of spiromesifen on chili fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Nasr (2014) [7] reported the residues on cucumber fruits collected after 1 hr, 1, 3, 5, 8, 11, 15 and 21 days from last spray and observed the residue half-life (RL 50 ) value of imidacloprid is 2.2 days. Similar type of study was conducted by Varghees, (2014) [11] who reported the dissipation of neonicotinoid insecticide, imidacloprid on chilli fruits drawn at 0, 1, 3, 5, 7, 15, 21 days after spraying with the half-life (RL 50 ) vale of 2.08 days.…”
Section: Resultsmentioning
confidence: 58%